ENTRE LA POLÍTICA EXTERIOR Y LA POLÍTICA INTERNA. DE LA PROCLAMA DE LA NEUTRALIDAD AL PLAN DE PAZ (1983-1989) - Cascante Segura, Carlos Humberto (2012)
Based on theconcept of the official memory, this article discusses the political internal objectives were pursued with the Costa Rican foreign policy elaborated between 1983 and 1989.For this purpose, the text establishes internal targets developed by the successive governments, of the period under study, attempted to achieve by means of its foreign policy. Also, the article analyzes the instruments used for such purposes. It concludes that the foreign policy of the period can not be seen only from the international stage, but had a significant impact within the country.